Magnetoresistance and electrical resistivity of N‐doped multi‐walled carbon nanotubes at low temperatures. Issue 6 (27th February 2015) - Ovsienko, I. V.; Len, T. A.; Matsuy, L. Yu.; Prylutskyy, Yu. I.; Berkutov, I. B.; Andrievskii, V. V.; Komnik, Yu. F.; Mirzoiev, I. G.; Grechnev, G. E.; Kolesnichenko, Yu. A.; Hayn, R.; Scharff, P.
Abstract The magnetoresistance and electrical resistivity of nitrogen‐doped multi‐walled carbon nanotubes (N‐MWCNTs) were studied in the temperature range of 1.6–100.3 and 1.6–286 K, respectively, using a standard four‐probe technique. The possible mechanisms of the observed effects are discussed in detail.